Effect of Eriocalyxin B on prostatic inflammation and pelvic pain in a mouse model of experimental autoimmune prostatitis. Issue 16 (23rd September 2020) - Zhang, Li‐Gang; Yu, Zi‐Qiang; Yang, Cheng; Chen, Jing; Zhan, Chang‐Sheng; Chen, Xian‐Guo; Zhang, Li; Hao, Zong‐Yao; Liang, Chao‐Zhao
Abstract: Background: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common disease in males. Eriocalyxin B (EriB), a natural diterpenoid purified from Isodon eriocalyx var. laxiflora, was previously reported to have antitumor effects via multiple immune‐related pathways. In this study, we investigated the effect of EriB on CP/CPPS using a mouse model of experimental autoimmune prostatitis (EAP) and explored its potential mechanisms. Methods: The EAP model was established in nonobese diabetic mice by intradermal injecting a mixture of prostate antigens and Complete Freund's Adjuvant on days 0 and 28. Then, EAP mice received daily intraperitoneal injections of EriB (5 or 10 mg/kg/d) for 14 days, from days 28 to 42 (EAP+EriB5 or EAP+EriB10 groups). The histopathological appearance of the prostate tissues was evaluated. Chronic pelvic pain development was assessed by cutaneous allodynia. Inflammatory cytokines were measured by enzyme‐linked immunosorbent assay tests. We then explored anti‐inflammatory potential mechanisms of EriB by studying the effects of PI3K inhibitor wortmannin (EAP+EriB10+Wort group) and NF‐κB inhibitor SC75741 (EAP+EriB10+SC group) on prostate inflammation and pelvic pain using this model. Results: Histological analyses revealed significant prostate inflammation in EAP mice compared with control mice. Significantly increased pelvic pain was detected in EAP mice ( P < .05). Compared with the EAP+Veh group, chronic pain development, histological appearance, and cytokine levels demonstrated that EriB could alleviate the severity of EAP in a dose‐dependent manner though upregulation of the PI3K/Akt/mTOR pathway and downregulation of the NF‐κB pathway. Further mechanism research demonstrated that the PI3K/AKT/mTOR pathway could be blocked by wortmannin, but was not affected by SC75741. In addition, the NF‐κB pathway could be further inhibited by SC75741 compared with the EAP+EriB10+Veh group. However, wortmannin could reactivate the NF‐κB pathway, indicating that the PI3K/AKT/mTOR pathway negatively regulates the NF‐κB pathway during EriB treatment. Conclusions: The results of the present study suggested that EriB could alleviate the severity of prostatic inflammation and pelvic pain in an EAP mouse model. These findings may broaden the value of EriB as a promising candidate for the treatment of CP/CPPS.